UJI KUAT TEKAN DAYA SERAP AIR DAN MASSA JENIS BATU BATA MERAH BERBAHAN TAMBAHAN ABU KULIT DAN JANGGEL JAGUNG DI WULUHAN JEMBER - Mei Sofiatul Hasanah; Yushardi Yushardi; Albertus Djoko Lesmono (Universitas Jember, 2021)
The increase in Indonesia's development activities increases people's consumption of more quality construction materials and is easy to reach in terms of price. Building materials with good quality can improve the quality of building construction. The increasing need of the community for building materials triggered the development of the brick-making industry. Redbrick is an element of building used in building construction made from clay base material with or without other mixed materials. This research is a type of experimental research. The purpose of this study is to know and analyze the composition of the addition of corn bark ash and ash corn cob appropriately to produce the quality of bricks with high compressive strength, low water absorption, and large density. Additional materials in this study in the form of corn bark ash and ash corn cob. The quality of red bricks is seen from three aspects, namely compressive strength, water absorption, and density. The largest compressive strength was obtained in the addition of ash corn cob by 2.5% by 37.2 Kg/Cm2 and the compressive strength of 49.5 Kg/Cm2 on the addition of corn skin ash by 2.5%. Water absorption measurement of all types of red bricks the results of the study showed all the results of water absorption is not eligible sni. The highest density was obtained from a mixture of 2.5% ash corn cob material of 17.5 gr/Cm3. the best composition to produce bricks with strong compressive value and high density and have low water absorption is 2.5% addition of ash corn cob and the addition of 2.5% corn skin ash. Keywords: Red bricks, strong press, water absorption, density.